2014
DOI: 10.3906/vet-1404-111
|View full text |Cite
|
Sign up to set email alerts
|

Clinical presentation and ultrasonographic findings in buffaloes with congestive heart failure

Abstract: The objective of this retrospective study was to describe the clinical presentation and ultrasonographic findings in water buffaloes suffering from congestive heart failure. Fifty-three buffaloes with congestive heart failure, which was confirmed postmortem, were included. The final diagnoses were traumatic pericarditis (n = 38) and vegetative endocarditis (n = 15). Ten healthy buffaloes were enrolled in this study as controls. The main clinical presentations were those related to right-sided congestive heart … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 22 publications
5
10
0
Order By: Relevance
“…Increased total proteins, globulins, liver enzymes J HELLENIC VET MED SOC 2017, 68(4) ΠΕΚΕ 2017 (AST, GGT) and total bilirubin were noticed. These findings were compatible with an inflammatory process that was attributable to advanced cardiac disease, impaired liver function, chronic infectious disease or other inflammatory complications (Tennant and Center, 2008) In the present study, impaired liver and renal function in TP group, indicating development of congestive heart failure (Hussein and Staufenbiel, 2014). Estimation of liver enzymes, total bilirubin, total proteins and albumin are helpful diagnostic techniques for evaluation of liver function (Tennant and Center, 2008).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Increased total proteins, globulins, liver enzymes J HELLENIC VET MED SOC 2017, 68(4) ΠΕΚΕ 2017 (AST, GGT) and total bilirubin were noticed. These findings were compatible with an inflammatory process that was attributable to advanced cardiac disease, impaired liver function, chronic infectious disease or other inflammatory complications (Tennant and Center, 2008) In the present study, impaired liver and renal function in TP group, indicating development of congestive heart failure (Hussein and Staufenbiel, 2014). Estimation of liver enzymes, total bilirubin, total proteins and albumin are helpful diagnostic techniques for evaluation of liver function (Tennant and Center, 2008).…”
Section: Discussionsupporting
confidence: 57%
“…Subsequent fibrin deposition will lead to fibrinous pericarditis and if fibrin within the pericardial sac matures to fibrinous tissue and fibrosis of the pericardium or epicardium then constrictive pericarditis will result (Perkins et al, 2004). Constrictive adhesions between epicardium and pericardium with fluid accumulation in pericardial sac impair the ability of the heart to act as a pump and result in congestive heart failure (Radostits et al, 2007;Hussein and Staufenbiel, 2014) or death of animal (Braun et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Various practical methods are used to assess diseases that affect the bovine respiratory system, including auscultation, percussion, blood ancillary tests, radiography, ultrasonography, and more invasive procedures such as pulmonary aspirations and biopsies [ 9 ]. Ultrasonography is a noninvasive tool that has been used frequently in diagnosis of cardiac diseases in buffalo [ 10 ]. Furthermore, ultrasonography is a good choice for imaging and describing suppurative pneumonia in cattle [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…This correlation was found within and between the groups of buffaloes. In the present study, no differences in probe placement were found between buffaloes and that previously mentioned in cattle and other studies (Slater & Herrtage 1995;Tharwat & Buczinski 2011;Hussein & Staufenbiel 2014). The four-chamber view was obtained from the right and left parasternal long-axes view when the probe was placed at the 4th ICS from the right or the 5th ICS from the left.…”
Section: Discussionmentioning
confidence: 45%
“…Correct positioning (advancement of the forelimbs) of the buffaloes allowed obtaining good quality images. Holding the legs up was not a good idea where the animals become less comfortable as well as this position led to a more caudal position of the triceps muscle mass, which results in obtaining poor quality images (Slater & Herrtage 1995;Tharwat et al 2012;Hussein & Staufenbiel 2014). The short-axes view was the most challenging view due to difficulties in obtaining symmetrical images and poor visualization due to hyperechogenicity of the pleural surface, especially in buffaloes with large body weights (Tharwat & Buczinski 2011).…”
Section: Discussionmentioning
confidence: 99%